The ultimate classic car book - Willson, Quentin (New York : DK Publishing, 1995)
Pictures and text highlight classic cars of the modern era with information on their designers and special features.
Includes index.
Notable/Best Books (A.L.A.).
Wilson's Junior High School.
Wilson's Senior High School.
Adult
Keywords: Antique and classic cars -- Collectors and collecting; Automobiles -- Pictorial works; Automobiles -- Pictorial works; Automobiles -- Collectors and collecting